EXPLORING THE INFLUENCE OF LEARNING INTENTION AND USMANI METHODS ON RECITING AL-QUR'AN IN HIGHER EDUCATION: DOES THE MEDIATION OF PEER TEACHING MATTER? - Saifudin, Ivan; Basuki, Basuki; Daryono, Rihab Wit (Abjadia : International Journal of Education, 2024)
This research aims to explore the urgency and influence of learning intention and the Usmani method on the ability to read the Al-Qur'an through peer teaching mediation. Conducted on 208 students at Ma'had Al-Jami'ah IAIN Ponorogo, this research used a quantitative approach with survey methods and non-probability sampling using purposive techniques. Data was collected through a questionnaire with a Likert scale and analyzed using descriptive statistical techniques and regression analysis to test hypotheses. It is hoped that the research results will provide valuable insight into the development of effective learning models for Islamic education, with relevant implications for formal and non-formal education. This research's recommendations include regular training for mahasantri and facilitators, the formation of structured learning groups, integration of technology in learning, as well as a mentoring program between senior and junior mahasantri. Thus, this research has the potential to increase the effectiveness of Al-Qur'an learning in Islamic religious education environments, strengthen the quality of interactions between students, and support the formation of deeper and more meaningful religious practices. Through its emphasis on Ottoman methods and peer teaching, this research not only enriches the understanding of Al-Qur'an learning but also makes an important contribution to curriculum development and teaching practices in the context of Islamic education.